ANALISIS PEMASARAN JAGUNG DAN DAYA BELT PETANI DI KABUPATEN TAKALAR SULAWESI SELATAN - , Sunanto; , Sahardi (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2008)
Analysis on Maize Marketing and Farmer Purchasing Power in Takalar Regency South Sulawesi. Agricultural development is very important as an activator of the national economy. Domestic resources need to be empowered to improve the welfare of farmer communities. The empowerment offers problems and opportunities. South Sulawesi is one of prominent maize production centers and one region that can become a maize production center is Takalar Regency. This research was conducted from June to October 2006 at Parasangan Beru Village and Bonto Lebang Village, North Galesong Sub-district in Takalar Regency. The research result shows that Takalar Regency area has potency for maize development. This is supported by natural and farmer resources, and the potency of Takalar Regency as a support of a metropolitan city (the marketing potency for agricultural products). The price of maize at the farmer level is feasible, this is reflected by the analysis research on price determination through the determination on the selling price cost. The welfare level of farmers (especially those with corn base) reaches a sufficiently good welfare level as it reaches an average of 2.57. Furthermore, the average net income of a farmer household reaches Rp.10,440,400/year. Key words: Make, purchasing capacity, marketing. Â Pembangunan pertanian sangat penting sebagai motor penggerak ekonomi nasional. Sumberdaya domestik perlu diberdayakan untuk peningkatan kesejahteraan masyarakat petani. Pemberdayaan tersebut memberikan dampak masalah dan peluang. Sulawesi Selatan merupakan salah satu sentra produksi jagung yang menonjol, salah satu daerah yang bisa dijadikan sentra produksi jagung adalah wilayah Kabupaten Takalar. Penelitian ini dilaksanakan pada bulan Juni hingga Oktober 2006 di Desa Parasangan Beru dan Desa Bonto Lebang Kecamatan Galesong Utara Kabupaten Takalar. Hasil Penelitian menunjukkan bahwa Wilayah Kabupaten Takalar mempunyai potensi untuk pengembangan jagung. Hal ini didukung sumberdaya alam, sumberdaya petani, dan potensi Kab. Takalar sebagai penyangga kota metropolitan (potensi pangsa pasar produk pertanian). Harga jagung yang berlaku di tingkat petani sudah layak, hal ini tercermin dari hasil analisis penentuan harga melalui penentuan harga pokok penjualan. Tingkat kesejahteraan petani (khususnya berbasis jagung ) mencapai tingkat kesejahteraan yang cukup bail karena mencapai rataan 2,57. selain itu juga rataan tingkat pendapatan bersih rumah tangga petani mencapai Rp.10.440.400/tahun.Kata kunci: Jagung, daya beli, pemasaran